Evaluation of oxidative stability, fatty acid profile and quality physico-chemical parameters of Brazil nut, coconut and Palm oils - Souza, Eliane Ferreira de; Silva, Ronaldo dos Santos; Santos, Mikaelly Nayara; Silva, Cinthia Aparecida de Andrade; Fiorucci, Antonio Rogério (Ciência e Natura, 2020)
The aim of this study was to assess the oxidative stability (OS) of oils Brazil nuts, coconut and palm, as well as determine the quality parameters: acid value (AV), humidity, ash content, and fatty acid profile (FA). According to the results the oils of Brazil nuts, coconut and palm oil showed AV of 2.02, 2.49 and 5.92 mg KOH g-1, humidity of 0.060, 0.101 and 0.040% and ash of 0.010, 0.005 and 0.009%, respectively. Considering FA, the Brazil nut oil showed greater amount of linoleic acid (38.61%) and oleic acid (31.95%) in its composition. While in coconut oil the major amounts were lauric acid (35.22%) and myristic (17.43%) and in the palm oil, oleic acid (48.30%) and palmitic (28.67%). The OS analysis showed that there is a relationship between the FA chemical composition of each oil and oxidative stability index (OSI) that relates to the resilience capacity to lipid degradation.